The forgotten patient: A psychological perspective on the implementation of bariatric surgery guidelines - Lynne Johnston; Kacey Jackson; Charlotte Hilton; Yitka Graham (Wiley, 2023)
Abstract There is strong evidence demonstrating the impact of bariatric surgery on weight‐loss and comorbidity improvement. In the UK, there is specific guidance to facilitate the assessment of a person's suitability for bariatric surgery. This paper highlights the clinical reality of routinely implementing this guidance, supported by literature and the perspectives of practicing psychologists. The consequences of the implementation of clinical guidelines within the context of the typical biopsychosocial profile of those referred for bariatric surgery are discussed. The ramifications of a screening approach rather than a clinical formulation‐based approach to assessment, impact of a possible unconscious bias in commissioning and an overemphasis on a biomedical model approach to treatment are also presented. These contextual factors are argued to contribute to a population of "forgotten patients" that is, patients who have been assessed as not suitable for bariatric surgery, and thus "stuck" in their journey toward better health. For these individuals the only option left are energy balance only approaches, which are the very same approaches to weight‐loss and comorbidity improvement that have been attempted, often for many years. Not only have these approaches not resulted in weight‐loss and health improvement, they also fail to address the underlying psychological causes of obesity. Consequently, this lack of support means that patients continue to suffer from poor quality of life, with no clear pathway to improved health and wellbeing. This paper illuminates the clear gaps in weight management service provision, the implementation of guidelines in practice, and offers practical suggestions to reduce the unintended consequences of clinical guidelines for bariatric surgery.